Distinct impacts of humidity profiles on physical properties and secondary formation of aerosols in Shanghai. (15th December 2021) - Liu, Tongqiang; He, Qianshan; Chen, Yonghang; Liu, Jie; Liu, Qiong; Fu, Xinshu; Zhang, Jiating; Huang, Guan; Li, Rui
Abstract: As a key component in the atmosphere, the increase in water vapor content can aggravate air pollution by promoting hygroscopic growth and secondary formation of aerosols. In this study, water vapor mixing ratio (WVMR) profiles retrieved from Raman lidar at night in Shanghai were used to evaluate the accuracy of a maintained microwave radiometer (MWR) and reanalysis datasets (ERA5 from ECMWF and MERRA-2 from NASA). The relative humidity (RH) profiles from radiosonde and reanalysis datasets were used to explore the influence of humidity vertical distributions on aerosol physical properties and secondary formation. There was a large WVMR difference between MWR and Raman lidar, with a mean bias (MB) and a root mean square error (RMSE) being 2.47 g/kg and 3.29 g/kg, respectively. However, the WVMR from ERA5 and MERRA-2 showed excellent agreement (correlation coefficients were both 0.94, N = 11288 and 3619, respectively) with that from Raman lidar and high accuracy especially MERRA-2, which are more suitable for meteorological and climatic applications than MWR. It was found that RH had a significant effect on the vertical distribution of aerosol extinction coefficient (AEC). Aerosol hygroscopic growth caused by high RH resulted in an obvious enhancement of AEC at 355 nm below 610 m in summer. As a good indicator for determining contribution of aerosol secondary formation, large ratios of PM2.5 to CO (PM2.5 /CO > 0.08) corresponded to high nitrogen oxidation ratios (NOR), sulfur oxidation ratios (SOR), and also high RH below 800 m during nighttime in winter, suggesting that RH and its vertical distribution played an important role in the aerosol secondary formation. The RH was high in the vertical direction when nitrate and sulfate mainly come from the secondary formation (NOR >0.1 or SOR >0.1), and in contrast to nitrate, the secondary formation for sulfates tended to depend on higher RH (>70%), which indicated that more stringent measures for nitrogen oxides emission reduction should be implemented in Shanghai to reduce the pollution of secondary aerosols in the future. Highlights: The water vapor from ERA-2 and MERRA-2 had high accuracy. The large AEC in summer below 610 m was caused by the aerosol hygroscopic growth. Secondary formation for aerosol especially sulfate required higher RH below 5 km.